KETERLIBATAN GEREJA KATOLIK INDONESIA DALAM BIDANG POLITIK - Yohanes Maryono (P3TK, Sanata Dharma University, 2012)
According to the second Vatican Council, the relationship between the Church and the world is that of two patterns in the Christian life itself, namely the relationship between her life as a part of the world and that of the Church. The relationship between the believers and the common life in the state is related to moral and social responsibility. The social activities of the Church is involvement, namely, participating in social struggles in order to accomplish human life and faith. It is to develop bonum commune. The placement of defense against human at the center of Catholic ecclesiology moves social involvement from the periphery to the center of life and the work of the Church. The second Vatican Council strengthens the local Church as social actors. The Indonesian bishops declare that Catholics in Indonesia is an integral part of the Indonesian nation in creating bonum commune.